PENGARUH MEDIA POSTER TERHADAP HASIL BELAJAR MATERI IPA SISWA KELAS III DI UPTD SDN PAMORAH - Latifah, Ummu; Hariyani, Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to find out whether there is an influence between poster media on the learning outcomes of class III science material at UPTD SDN Pamorah, to find out whether there is an influence between poster media on interest in learning science material for class III at UPTD SDN Pamorah. This research uses quantitative research. The place taken in this research was UPTD SDN Pamorah, Tragah sub-district. The population in this study was all 36 class III students. The sample in this study was 16 female students and 20 male students. The instrument in this research used test questions. The data collection technique in this research is in the form of test questions.